A REVIEW OF FACTORS AFFECTING BUILDING DEFECTS IN SINGAPORE - Po Seng Kian (Civil Engineering Dimension, 2001)
In developing countries, building maintenance technology is currently vastly underrated and ignored by owners, managers, and professionals. The building and construction authority of Singapore (BCA) has identified that the complaints about building defects have gone up in recent years with common problems such as leaky roof and walls, floor defect, and improper outlet pipe. This paper presents a brief description on building defect in use for commercial building as well as residential buildings in Singapore. The main objective is to highlight the important problems and suggest a greater participation of professionals in building maintenance. It also provides some site investigations photographs of various defects, which is expected to be useful for builders, architects, and others who deal with building materials.